In situ templating of PbS nanorods in reverse hexagonal liquid crystal - Huang, N.M.; Shahidan, R.; Khiew, P.S.; Peter, L.; Kan, C.S. (Elsevier, 2004)
We report the in situ templating of lead sulfides (PbS) with mean diameter of 5.7 Â± 1.0 nm in the reverse hexagonal phase liquid crystal using lead nitrate and thioacetamide as the reactants. The texture of the reverse hexagonal phase for before and after PbS growth does not varies as observed under polarizing microscope indicating direct templating of PbS in hexagonal liquid crystalline phase. This result is consistent with measurement using small-angle X-ray scattering (SAXS). X-ray photoelectron spectroscopy (XPS) has been carried out to confirm the formation of PbS and energy filter transmission electron microscopy (EFTEM) observations show the size and shape of the PbS particles. The templated PbS nanorods show blue shift compare to the bulk material when characterized using UV-vis-NIR spectroscopy. Â© 2004 Elsevier B.V. All rights reserved.